PENGARUH KEPUASAN PELANGGAN TERHADAP KOMITMEN DAN LOYALITAS PELANGGAN PENGGUNA BAJA RINGAN PADA ADRIAN PRATAMA PUTRA - Hendrikus Herryanto; I Gede Riana (Journal of Applied Management Studies, 2021)
The purpose of this study was to determine (1) the effect of customer satisfaction on customer commitment of light steel users at Adrian Pratama Putra in Denpasar City; (2) the effect of customer satisfaction on customer loyalty of Baja Ringan users at Adrian Pratama Putra in Denpasar City; and (3) the influence of customer commitment on customer loyalty of Baja Ringan users at Adrian Pratama Putra in Denpasar City. The research method used is quantitative research methods with the type of research cinfirmatory research. The research sample was 100 Adrian Pratama Putra customers in Denpasar City, selected by accidental sampling. The data analysis used was Partial Least Square (PLS) analysis. The results showed that (1) Customer satisfaction has a positive and significant effect on customer commitment of Baja Ringan users at Adrian Pratama Putra in Denpasar City; (2) Customer satisfaction has a positive and significant effect on customer loyalty of Baja Ringan users at Adrian Pratama Putra in Denpasar City; and (3) Customer commitment has a positive and significant effect on customer loyalty of Baja Ringan users at Adrian Pratama Putra in Denpasar City.